Proverbs, Job, and Ecclesiastes in the Septuagint (LXX) - Pouchelle, Patrick (The Wiley Blackwell companion to wisdom literature, 2020)
This chapter deals with the Septuagint, in particular with the Greek translation of Proverbs, Job, and Ecclesiastes. It introduces the reader first to the main issues associated with the study of the Septuagint as a produced translation from Hebrew to Greek, as well as a received Greek text in its own right. One of the major shifts observed in these translated texts is how the Septuagint presents a divine revealed wisdom where the Hebrew texts are more concerned with a profane, experiential type of wisdom. As this chapter also shows, each of the translations possesses certain characteristics which differentiate it from other books of the Septuagint. The Greek Proverbs is a translation whose aim is to put forward its own interpretation of the Hebrew. The Greek text of Job is a type of rewriting of its Hebrew original. The Greek text of Ecclesiastes is a slavish, literal translation.